Spaceborne detection of XCO2 enhancement induced by Australian mega-bushfires - Jun Wang; Zhiqiang Liu; Ning Zeng; Fei Jiang; Hengmao Wang; Weimin Ju (Environmental Research Letters, 2020)
The 2019–20 Australian mega-bushfires, which raged particularly over New South Wales and Victoria, released large amounts of toxic haze and CO _2 . Here, we investigate whether the resulting CO _2 enhancement can be directly detected by satellite observations, based on National Aeronautics and Space Administration’s Orbiting Carbon Observatory-2 (OCO-2) column-averaged CO _2 (XCO _2 ) product. We find that smoke from wildfires can greatly obscure satellite observations, making the available XCO _2 mainly locate over outer fringes of plumes downwind of the major mega-bushfires in eastern Australia in three orbit observations during November–December 2019, with their enhancements of approximately 1.5 ppm. This fire-induced CO _2 enhancement is further confirmed using an atmospheric transport model, Goddard Earth Observing System-Chem, forced by satellite observation-derived fire product Global Fire Emissions Database, version 4.1 and wind observations, with comparable simulated XCO _2 enhancements. Model simulation also suggests that the sensitivity of the downwind maximum XCO _2 enhancement is 0.41 $ ± \,$ 0.04 ppm for 1 TgC d ^−1 fire emissions. In sum, though detectable to some extent, it remains a challenge to get the accurate maximum XCO _2 enhancements due to the gaps in XCO _2 detections obscured by smoke. Understanding the capability of OCO-2 XCO _2 detection is prerequisite for monitoring and constraining wildfire CO _2 emissions by inversions.